A preliminary validation of PMQ—A four-factor questionnaire measuring parental mentalizing - Teräsahjo, Timo; Turunen, Tiina; Lahtinen, Oskari; Salmivalli, Christina (Frontiers in Psychology, 2024)
The present study describes the construction and preliminary validation of a new parental mentalizing scale, PMQ. Based on theory, we hypothesized that one higher-order parental mentalizing factor would comprise four dimensions of parental mentalizing: 1) Parental selfmentalizing (SELF), 2) Parental child-mentalizing (CHILD), 3) Effort (E), and 4) Curiosity (C). After modifying the content of one factor (Effort > Lack of Effort, LE), four-factor structure with one higher-order factor was confirmed in data collected from parents of children aged two to six years through social media and email lists (N = 321, 10% male). All factors loaded significantly on the higher-order factor, with acceptable internal consistencies. Next, PMQ factors were compared to the factors of a previously validated questionnaire, Parental reflective functioning questionnaire (PRFQ). PMQ and PRFQ factors correlated consistently and significantly, indicating the validity of the PMQ as a measure of parental mentalization ability. The continuation of PMQ validation is discussed.